Peningkatan Motorik Kasar Anak Melalui Senam Fantasi - Setiawati, Yeni (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2023)
Problems of this thesis do with fantasy gymnastic can uplift skill harsh motorik at group child of B1 TK Negeri Pembina Selupu Rejang?. As for intention of this research that is to increase skill of harsh motorik through fantasy gymnastic at group child of B1 TK Negeri Pembina Selupu Rejang. With this research subjek group of B TK Negeri Pembina Selupu Rejang amounting to 20 one who consist of 10 daughter and 10 boy. This research consist of two cycle. Analysis technique the used by using simple statistical in the form of percentage. From result of obtained to research happened the make-up of result of ability of this matter fantasy gymnastic seen at cycle 1 I ability of child fantasy gymnastic only 7 child people from 20 child people with average value 64,75%, while cycle of II this researcher add technique that is with fantasy gymnastic according to story to be child become more motivated again, its result ability of child fantasy mount that is 17 child people with average value 81.5%. From result of this research can be concluded that with activity of fantasy gymnastic can improve domination of harsh motorik of child.